Efektivitas Penggunaan Media Youtube dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti Kelas IV SDN 34 Pontianak Selatan - Ma'ruf; Fernanda, Ryan; Ardiansah, Roni (QuranicEdu: Journal of Islamic Education, 2025)
This study was motivated by students' learning outcomes that did not meet the Minimum Mastery Criteria (KKM). The learning of Islamic Religious Education and Character Education is still conducted conventionally, resulting in suboptimal learning outcomes and low student enthusiasm during lessons. This research aims to measure the effectiveness of using YouTube video media to improve students' learning outcomes. The research employs a quantitative approach with an experimental method using a quasi-experimental design. Data were collected through tests, observations, and documentation using test sheets, observation sheets, and documentation sheets. The data were analyzed using descriptive quantitative analysis. The results indicate that the use of YouTube media consists of two stages: design and implementation. The design stage includes creating educational videos, uploading the videos to the YouTube application, and explaining the steps for using the media. The implementation stage occurs during the learning process, including opening activities, the core activities (using YouTube media), and closing activities. The use of YouTube media during learning runs smoothly. The analysis of student learning outcomes in the experimental class showed an average pretest score of 5.429 and a posttest score of 7.571, while the control class had a pretest score of 5.200 and a posttest score of 6.257. The effectiveness of YouTube media on students' learning outcomes was 20%.